Aryl 4-monooxygenase and cytochrome P-450 in the aorta: possible role in atherosclerosis. - Juchau, M R (1976)
Aryl 4-monooxygenase [aniline, reduced-flavoprotein:oxygen oxidoreductase (4-hydroxylating); EC 1.14.14.1] activity was searched for and found in homogenates of aorta walls from rabbits, rhesus monkeys, and humans. Specific activities were comparable to activities observed in several other extrahepatic tissues of rabbits and monkeys and in epidermal tissues from mice, but were one to two orders of magnitude lower than those observed in corresponding preparations of hepatic tissues. Cytochrome P-450 also could be detected in low concentrations in microsomal fractions of aortic wall homogenates. The monooxygenase activity found in the aorta could play a significant role in the etiology and pathogenesis of atherosclerosis in humans by catalyzing the conversion of environmental promutagens to mutagenic initiators and/or cytotoxic factors, thus leading to development of benign, smooth muscle tumors of the inner lining of artery walls.